THE SUN COLLECTORS, THEIRS CLASSIFICATION, IN THEM OBSERVE TO BE USED DISADVANTAGES AND SOLUTIONS - Siddikov Rasuljon Oktamovich; Mirzayev Islombek Umarali o'gʻli (American Journals, 2023)
This in the macula It’s dark of collectors historical, their classification, Kuyosh in collectors observed defects and drinks in Tugri information given